Analisis Semiotika Roland Barthes pada Kain Songket Silungkang Kota Sawahlunto Provinsi Sumatera Barat - Iswandi, Heri; Didiek Prasetya; Shalyna Nadya Amalia (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Silungkang Songket is one of the crafts of the people of Sawahlunto City which is a superior product in the area. The specialty of Minangkabau songket cloth, especially in the Silungkang area, lies in its very diverse motifs, including the rangkiang motif, the pucuk rebung motif, the bungo canngkeh motif, and so on. Each of these motifs has its own name and meaning, and usually the motifs applied are inspired by plants, animals or objects in the surrounding nature. This study aims to read the elements of signs in Silungkang Songket cloth by choosing one decorative motif as a case study using Roland Barthes' semiotic concept, namely through the analysis of the sign system in the form of denotation, connotation, and myth. The research method used is a qualitative approach with a descriptive nature. The results of this study indicate that Silungkang Songket cloth is not just a physical object, but also a sign system that reflects social and cultural values. This study also reveals how the Minangkabau people give symbolic meaning to the cultural work. Roland Barthes' semiotic analysis of Silungkang songket cloth shows that every visual element in the cloth not only functions as an aesthetic decoration, but also as a cultural sign that contains layered meanings. And finally, when viewed from the mythological element, the rangkiang motif on the songket cloth serves to strengthen the Minang cultural narrative about harmony, welfare, and social order based on custom and religion.